DINAMIKA INTERNALIZED SEXUAL STIGMA PADA LESBIAN MASKULIN YANG BELUM MENGALAMI PROSES COMING OUT (STUDI KASUS PADA DUA LESBIAN MASKULIN DI JAKARTA) - Rr. Sitti Hendrianti Sarahsita; Lidia Laksana Hidajat (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2017)
The stigma faced by lesbian groups might form an internalized sexual stigma. Internalized sexual stigma is a condition of a person who has internalized the stigma given by the society into herself. It can affect the psychological well-being of a lesbian. This research was aimed to describe the internalized sexual stigma on masculine lesbian women who have not disclosed their sexual identity. A qualitative approach was used as the research method by conducting interviews and psychological measurement tools such as Thematic Apperception Test and Drawing Tests (WZT, DAP, BAUM). Taken using snowball sampling method, two masculine lesbian women were involved in this research. The results of the analysis obtained illustrated that both participants had internalized sexual stigma due to two main factors. The first factor is contributed by internal factors such as psychological needs and personality aspects, whereas the second are external factors, that comprehends the rejection and discrimination faced by both participants and moreover deals with sexual stigma in their family and work environment. Expected research on sexual stigma can be used as an understanding of the needs and the condition of lesbians in Indonesia. In addition to the issue of stigma, further research about the mental health conditions associated with sexual stigma occurred among lesbians would be a necessity.